Ultrasonic diagnosis of perinatal lethal hypophosphatasia. (August 2013) - Muller, Linnie; Wainwright, Helen; Beighton, Peter
Perinatal lethal hypophosphatasia (PLH) [OMIM 241500] is transmitted as an autosomal recessive trait, with a significant risk of recurrence for further offspring following the birth of an affected baby. The study was aimed at documentation of the ultrasonographical manifestations of PLH at the 13th week of gestation, confirming that these appearances are consistent with those in later pregnancy (20 weeks) and demonstrating that they correlate with the radiographical and histological features. In clinical practice, these observations facilitate the early ultrasonic diagnosis of PLH in a potentially affected foetus. The ultrasonographical appearances in siblings at 13 and 20 weeks' gestations were documented and compared. Post-mortem studies including babygram and histology were undertaken in these foetuses. Autopsy details of a third foetus were available from the pathology archives. The results showed that the ultrasonographical, clinical, radiological and histological appearances correlated in each instance. Thus, it was concluded that ultrasonographical diagnosis of PLH is possible as early as the 13th week of gestation.